Intracranial fat migration: A newly described complication of autologous fat repair of a cerebrospinal fluid leak following supracerebellar infratentorial approach. (2015) - Ludwig, Cassie A.; Aujla, Parvir; Moreno, Mario; Veeravagu, Anand; Li, Gordon
Graphical abstract: Magnetic resonance imaging of postoperative autologous adipose tissue graft repair. T2 axial demonstrates the epidural fat inside the subarachnoid, and the intraparenchymal space of the occipital lobe, extending into the basal cistern, prepontine cistern, and ventricle. Highlights: We examine a case of fat graft migration following autologous fat repair of a cerebrospinal fluid (CSF) leak that occurred after a supracerebellar infratentorial approach. Symptoms from migration resolved with supportive care. Physicians should be aware of the possibility of autologous fat migration when explaining fat graft CSF leak repair to patients. Physicians should consider supportive care when autologous fat migration occurs. Abstract: Introduction: Intracranial fat migration following autologous fat graft and placement of a lumbar drain for cerebrospinal fluid leak after pineal cyst resection surgery has not been previously reported. Case presentation: The authors present a case of a 39-year-old male with a history of headaches who presented for removal of a pineal cyst from the pineal region. He subsequently experienced cerebrospinal fluid leak and postoperative Escherichia coli (E. Coli) wound infection, and meningitis, which were treated initially with wound washout and antibiotics in addition to bone removal and primary repair with primary suture-closure of the durotomy. A lumbar drain was left in place. The cerebrospinal fluid leak returned two weeks following removal of the lumbar drain; therefore, autologous fat graft repair and lumbar drain placement were performed. Three days later, the patient began experiencing right homonymous hemianopia and was found via computed tomography and magnetic resonance imaging to have autologous fat in the infra‑ and supratentorial space, including intraparenchymal and subarachnoid spread. Symptoms began to resolve with supportive care over 48 hours and had almost fully resolved within one week. Discussion: This is the first known report of a patient with an autologous fat graft entering the subarachnoid space, intraparenchymal space, and ventricles following fat graft and lumbar drainage. Conclusion: This case highlights the importance of monitoring for complications of lumbar drain placement.